Letter : Spanish Civil War - Elvin, Herbert Henry
010-0130-001 NATIONAL UNION of CLERKS & ADMINISTRATIVE WORKERS. TRADE UNION No. 916. APPROVED SOCIETY No. 184. HOLborn 1733 Telegrams: "UNICLERKOS. PHONE. London." REGISTERED OFFICE : 17-20, Holborn Hall Gray's Inn Road London. W.C.1. WHEN REPLYING PLEASE QUOTE : Your Ref.: WMC/FEM/FP/416 Sec.'s Dept. Our Ref. : 65/1/5. Sir Walter Citrine, Trades Union Congress General Council, Transport House, SMITH SQUARE, S.W.1. All communications to be addressed to The General Secretary. Write a separate letter for each subject dealt with. 17th August, 1936. Dear Sir Walter, SPANISH CIVIL WAR. I am in receipt of your letter of the 15th instant, for which I am much obliged. This morning's news is not cheerful. Yours sincerely, Herbert H. Elvin GENERAL SECRETARY. 292/946/10/142